Asymmetric and Hybrid Warfare in Postmodern Times: Lesson from Hezbollah-Israeli War 2006 - Estriani, Heavy Nala; Dewanto, Pamungkas Ayudaning; Asyidiqi, Hasbi (Andalas Journal of International Studies (AJIS), 2023)
This paper discussed asymmetric warfare between Hezbollah as a non-state actor against Israel in the Second Hezbollah-Israeli War in 2006. This paper focused on Hezbollah's strategy as the weaker side to fight against Israel as the state with the strongest military forces in the Middle East. The battle between Hezbollah and Israel can be categorized as post-modern warfare because it has hybrid and irregular elements of warfare. That is, the war mixes the use of conventional and non-conventional methods of warfare. This paper uses the concept of hybrid warfare and Taylor’s strategy theory to explain the Hezbollah strategy against Israel. The main objective of this paper is to analyze and explain the strategies employed by Hezbollah, a non-state actor, in the Second Hezbollah-Israeli War in 2006, utilizing the concepts of asymmetric and hybrid warfare. The paper focuses on Hezbollah's use of post-modern strategies, such as guerrilla tactics, unconventional warfare methods, information warfare, and psychological tactics, to counter the Israeli Defense Force (IDF) and achieve its goals in the asymmetric conflict. This paper finds that Hezbollah uses elements of post-modern strategy by conducting guerrilla and hide-and-seek tactics, mixing the use of conventional and modern warfare equipment, the use information and media, engaging in acts of terror, and applying psychological warfare to achieve the ultimate goal the main objective) in the fight against Israel Defense Force (IDF).